If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 19y = -7 Solving 3x + 19y = -7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-19y' to each side of the equation. 3x + 19y + -19y = -7 + -19y Combine like terms: 19y + -19y = 0 3x + 0 = -7 + -19y 3x = -7 + -19y Divide each side by '3'. x = -2.333333333 + -6.333333333y Simplifying x = -2.333333333 + -6.333333333y
| 2(2x+9)=38 | | X-3=13-3x | | X+3x+4(x-1)=-12 | | 0.6x+5.3=4.4 | | 0.6+5.3=4.4 | | -2=3m-5m | | 2cos^2x+sinx=5 | | 3(x-2)=3x+12 | | 2-3x(x-1)= | | 70-(3x+50)=2-5x | | x/17-7x/17=30/17 | | W-10=-25 | | 2+3(x-2)=5x-10 | | 0.7x-7.7(3.6+3.7x)=-241.703 | | X/11=-2/13 | | -4(x+2)=-63 | | 3x+9x-12=180 | | R-11=3 | | -125.994=-6.9(-2.8n-3.3) | | 3(x-6)-4x=20 | | -12+2y=10 | | X+7X^2-63=8 | | 125.994=-6.9(-2.8n-3.3) | | 4x^2+72x+308=0 | | -82.93884=5.8(2.38k-1.9) | | f(x)=-x^2-x+6 | | 2a+4b+8c= | | x+2(x-6)=x-11 | | 3(6+8)=48 | | 2a+4b+15= | | 2a+4b-15= | | 2(9x+5)=12x-2 |